2017
DOI: 10.1097/meg.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies and antigens against hepatitis A–E viruses in refugees and asylum seekers in Germany in 2015

Abstract: The prevalence of refugees with previous exposure to hepatitis viruses was higher than that in the general German population, but lower than in other migrant populations in Germany. The vaccination status against hepatitis B was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
7
31
1
4
Order By: Relevance
“…Still, the overall range of anti‐HEV frequencies is in line with other studies from Europe and North America, which suggests similar HEV reservoirs and modes of transmission across different regions and countries. Even when refugees were evaluated, similar rates were found …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Still, the overall range of anti‐HEV frequencies is in line with other studies from Europe and North America, which suggests similar HEV reservoirs and modes of transmission across different regions and countries. Even when refugees were evaluated, similar rates were found …”
Section: Discussionsupporting
confidence: 56%
“…Even when refugees were evaluated, similar rates were found. 31 More important, HEV RNA was negative in all anti-HEV positive women. Hence, as no positive PCR samples were found, anyone could reason that the samples that were frozen in a −80°C freezer for a long period would denature the HEV RNA.…”
Section: Geographical Differencesmentioning
confidence: 96%
“…Like us, Rein et al found the prevalence of HBsAg to be lowest among refugees from the Middle East and highest among those from Africa and Asia . Male asylum seekers in Germany were almost twice as likely as females to be positive for HBsAg . Foreign born Asians attending college in the United States had an 81% prevalence of HBsAb and a 16% rate of susceptibility to hepatitis B, similar to the 77% and 22%, respectively, found among the adult refugees presented here .…”
Section: Discussionsupporting
confidence: 84%
“…85% of Syrian and 100% of Eritrean asylum seekers in the Netherlands had HAV Ab, and immunity increased with age . Among refugees being held in detention in Germany, 91.2% were positive for HAV Ab . Like us, Rein et al found the prevalence of HBsAg to be lowest among refugees from the Middle East and highest among those from Africa and Asia .…”
Section: Discussionmentioning
confidence: 69%
“…Most children may have natural immunity from prior HAV infection acquired at their country of origin whereas others may be non-immune and candidates for vaccination against HAV. In a study in refugees and asylum seekers in Germany on the immunity against hepatitis A-E viruses, 81% of refugee minors were immune, which corresponds to the high anti-HAV seroprevalence rates in patients from Sub-Saharan and Northern Africa, and from the Middle East [64]. The U.S. CDC and AAP recommends the hepatitis A vaccine as part of the routine immunization schedule for all children aged 1 year and older without evidence of immunity [23].…”
Section: Hepatitis Amentioning
confidence: 99%